Association of low-density lipoprotein/high-density lipoprotein ratio with cognition, Alzheimer’s disease biomarkers and brain structure - Zihao Zhang; Lingzhi Ma; Liangyu Huang; Yangke Zhu; Haihua Guo; Lanyang Wang; Wei Zhang; Lan Tan (Frontiers in Aging Neuroscience)
BackgroundThe relationship between the low-density lipoprotein/high-density lipoprotein (LDL/HDL) ratio, an indicator of lipid metabolism and assessment of cardiovascular disease (CVD) risk, and Alzheimer’s disease (AD) is unclear.MethodsMultivariable Cox regression analyses were used to examine the association of LDL/HDL ratio and the risk of AD. Multiple linear regression and mixed effects models used to assess associations between LDL/HDL and cognitive function, AD pathology, and brain structure. Mediation analyses examined AD pathology’s potential mediating role between the LDL/HDL ratio and cognition.ResultsHigher LDL/HDL ratio correlated with lower AD risk (HR 0.644 [0.431, 0.962]). In the linear regression analyses, the LDL/HDL ratio were positively associated with cognition. Longitudinally, the LDL/HDL ratio also positively with cognitive measures. Besides, higher LDL/HDL ratio were associated Aβ42 and decreased Tau, pTau, Tau/Aβ42, pTau/Aβ42, and pTau/Tau. The LDL/HDL ratio was positively associated with brain structures such as hippocampal volume. Mediation analyses revealed AD pathology mediated the association between LDL/HDL ratio and cognition.ConclusionThe LDL/HDL ratio is associated with AD risk, cognition, AD biomarkers and brain structure and can affect cognition by AD biomarkers.